Transtextualidade entre Sófocles e Ovídio: virtude e ira na caracterização de Ájax - Almeida, Felipe dos Santos (2017)
This work aims at studying the intertextuality between Ovid’s Metamorphosis and Sophocles’s play, Aias. This work of Comparative Literature focus on the characterization of the hero Ajax. However, our analysis limits this characterization to two issues, present on Classical Literature heroes: the virtue, especially, belligerent, and the wrath. To achieving such purpose, firstly, we point how those issues are present on the archaic Greek literature tradition of the studied hero, particularly, in Homeric poems, which introduce, in a pioneer way, a singular characterization. In these Homeric works, this character is already remarkable by his warrior virtue and by his intense wrath. Secondly, we analyze Ovid and Sophocles’ literary works separately aiming at understanding the consequence of those two issues in the characterization of such hero and in the semantic purpose of episodes in each work. At last, we introduce Genette’s theory about intertextuality, which he names transtextuality, and in which he bounds a tipology to restrict its many types of operations. Based on that theory, we present the operations, fulfilled by the latin author, that verify such transtextual issue in his epic poem, specially, related to Sophocles’ play. Nevertheless, they are restricted to the way such operations act to compose the characterization of the belligerent and fiery hero Ajax. To understanding the literary works and the following analysis better, we present a general translation from the corpus mentioned on the present work.